2015
DOI: 10.1371/journal.pone.0139096
|View full text |Cite|
|
Sign up to set email alerts
|

B-Cell Responses to Human Bocaviruses 1–4: New Insights from a Childhood Follow-Up Study

Abstract: Human bocaviruses (HBoVs) 1–4 are recently discovered, antigenically similar parvoviruses. We examined the hypothesis that the antigenic similarity of these viruses could give rise to clinically and diagnostically important immunological interactions. IgG and IgM EIAs as well as qPCR were used to study ~2000 sera collected from infancy to early adolescence at 3–6-month intervals from 109 children whose symptoms were recorded. We found that HBoV1-4-specific seroprevalences at age 6 years were 80%, 48%, 10%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…3a), whilst in our previous study, some children with the same combination did present OAS (Kantola et al, 2015). This was shown by identical IgG curves in the blocked and unblocked EIAs (Fig.…”
Section: No Significant Boost After Sequential Inoculation By the Samsupporting
confidence: 60%
See 1 more Smart Citation
“…3a), whilst in our previous study, some children with the same combination did present OAS (Kantola et al, 2015). This was shown by identical IgG curves in the blocked and unblocked EIAs (Fig.…”
Section: No Significant Boost After Sequential Inoculation By the Samsupporting
confidence: 60%
“…In another recent serological study of constitutionally healthy children followed for many years, several PCR-confirmed heterotypic secondary infections were observed with inefficient or no specific IgG responses against the second virus type. Instead, a vigorous recall response appeared against the first virus type (Kantola et al, 2015). Priming with one HBoV type may thus inhibit the subsequent generation of antibodies towards the unique epitopes of another HBoV type -a phenomenon known as 'original antigenic sin' (OAS) (Francis, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…The cross-reactivity can be visualized by blocking the serum with heterologous HBoVs prior to the EIA. To identify such cross-reactivity is a prerequisite for correct interpretation of the HBoV EIA results1929. The human bufavirus genotypes differ by 27–36% in VP24, and in our EIA analysis the BuV genotypes were not cross-reactive.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, if the primary infection of the host is local and superficial, it might not induce a strong long-lasting antibody response. With HBoVs it has been shown that exposure to homo- or heterologous HBoV species may boost the antibody response2829. Thus, the similar BuV seroprevalence among Finnish adults and children might be a consequence of the general rarity of BuV infections in the Nordic countries, leading to inadequate maintenance of antibody responses.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, serological studies initially indicated that around 100% of the adults had antibodies against human bocavirus, which led to propose that newborns are protected by maternal antibodies [36][37][38]. Recently, however, cross reactions and a phenomenon called "original antigenic sin" have been reported to occur among different types of human bocaviruses (at present 4 genotypes have been identified: HBoV1 associated with respiratory infection and HBoV2-4 associated with infection of the enteric tract but currently not related to disease) [11,[39][40][41]. As a result, infection with one HBoV type induces antibodies that can react with a different type of HBoV.…”
Section: Discussionmentioning
confidence: 99%